Maf deficiency in T cells dysregulates T(reg) - T(H)17 balance leading to spontaneous colitis - Imbratta, Claire (Sci Rep, 2019)
The maintenance of homeostasis in the gut is a major challenge for the immune system. Here we demonstrate that the transcription factor MAF plays a central role in T cells for the prevention of gastro-intestinal inflammation. Conditional knock out mice lacking Maf in all T cells developed spontaneous late-onset colitis, correlating with a decrease of FOXP3(+)RORγt(+) T cells proportion, dampened IL-10 production in the colon and an increase of inflammatory T(H)17 cells. Strikingly, FOXP3(+) specific conditional knock out mice for MAF did not develop colitis and demonstrated normal levels of IL-10 in their colon, despite the incapacity of regulatory T cells lacking MAF to suppress colon inflammation in Rag1(−/−) mice transferred with naïve CD4(+) T cells. We showed that one of the cellular sources of IL-10 in the colon of these mice are T(H)17 cells. Thus, MAF is critically involved in the maintenance of the gut homeostasis by regulating the balance between T(reg) and T(H)17 cells either at the level of their differentiation or through the modulation of their functions.